Qira'atul Qur'an Program in Building Religious Character at the High School of the Pancasila Education Foundation (YPP) Sawit Seberang - M. Sani Hafiz Rusydi; Zailani Zailani (MASI Mandiri Edukasi, 2026)
Religious character education remains a challenge in secondary schools due to students’ declining discipline in worship practices and limited internalization of Qur’anic values in daily behavior. To address this issue, schools implement religious habituation programs such as the Qira'atul Qur'an Program. This study aims to describe the implementation of the Qira'atul Qur'an Program, analyze its role in strengthening students’ religious character, and identify the supporting and inhibiting factors in its implementation at SMA Yayasan Pendidikan Pancasila (YPP) Sawit Seberang. This research employed a qualitative, descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving the principal, Islamic Education teachers, religious mentors, and students. The results indicate that the Qira'atul Qur'an Program is implemented routinely and systematically before formal learning activities through habituation, talaqqi, and tahsin methods. The program contributes significantly to strengthening students’ religious character, as reflected in improved worship discipline, emotional calmness, polite behavior, and increased affection for the Qur'an. Supporting factors include strong institutional support, teachers’ commitment, and a conducive religious school environment, while inhibiting factors involve students’ diverse Qur'anic reading abilities and limited time allocation. Overall, the Qira'atul Qur'an Program plays a positive role in reinforcing religious character education at the secondary school level.